Surkh potli aur dosri khaniyan - Fozia tahir (Ferozsons (PVT) LTD Lahore, 1997)
Surkh Potli Aur Dosri Khaniyan is a collection of captivating short stories, weaving together themes of mystery, morality, and life lessons.